Metakroni karcinom larinksa prikaz slučaja = Metachronous laryngeal cancer : a case report - Grabovac, Stjepan; Grabovac, Đurđica; Puharić, Zrinka; Begić, Jasna (2019)
Cilj: Ukazati na potrebu trajnog praćenja pacijenata kod kojih je zbog karcinoma učinjena parcijalna laringektomija. Prikaz slučaja: Prikazali smo pacijenta koji je u vremenskom razmaku od dvadeset godina tri puta imao karcinom larinksa. 1982. godine učinjena je parcijalna laringektomija. Drugi primarni tumor nastao je na sluznici ostatka larinksa 2000. godine, kada je učinjena traheotomija i laringofisura s ekscizijom tumora. Treće javljanje tumora bilo je 2002. godine kada je učinjena retraheotomija i totalna laringektomija. U sva tri javljanja radilo se o planocelularnom karcinomu. Pacijent je od 2000. godine bio pod redovitom kontrolom, a preminuo je 2013. godine u dobi od 85 godina. Zaključak: Pojava planocelularnog karcinoma larinksa moguća je godinama nakon uspješnog liječenja početnog tumora. Objašnjenje nalazimo u ostatku sluznice koja je obilježena poljima kancerizacije, što čini podlogu za nastanak novih tumora.
Aim: To point out the need for permanent monitoring of patients with partial laryngectomy due to cancer. Case report: We have shown a patient who has had the laryngeal cancer three times at intervals of twenty years In 1982, a partial laryngectomy was performed. The second primary tumour was formed on the mucosa of the rest of the larynx in 2000, when the tracheotomy and laryngofissure were performed. The third tumour incidence was in 2002, when retracheotomy and total laryngectomy were performed. In all three cases, there was the case of a planocellular carcinoma. The patient was regularly checked-up since 2000, but he passed away in 2013 at the age of 85. Conclusion: The appearance of the laryngeal planocellular carcinoma is possible years after the successful treatment of the primary tumour. The explanation is found in the remains of the mucosa, which is marked by the field of cancerisation, which is the basis for the incidence of new tumours.
Bibliografija: 27 jed.
Sažetak ; Abstract.
Keywords: Metakroni karcinom larinksa -- Karcinom larinksa -- Laringektomija; Prikaz slučaja